PENERAPAN MODEL TAI (TEAM ASSISSTED INDIVIDUALLY) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEKAYAAN SUMBER ENERGI DI INDONESIA DI SDN ILOT - Nasri Diana (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
This study aimed to determine the increase in student learning outcomes on the material wealth of energy sources in Indonesia after students learned through the application of the TAI model. The research method used was a qualitative one using the CAR model which consisted of the planning stage, the implementation stage, the observation stage and the reflection stage. The population of this study was class IV students of SDN Ilot, the second semester of the academic year 2019/2020. The sampling technique was done by random sampling which was IV, totaling 18 students. Data collecting was carried out by observation, interviews, test questions with questions in the form of choose and essay and documentation. Data processing was done by data tabulation and data interpretation. The results showed that the acquisition of student learning outcomes was seen with the average value in cycle I was 65 and cycle II was 82.2 while student learning completeness in cycle I was 27.7% and cycle II was 100%. So it could be said that the increase in student learning outcomes on the material wealth of energy sources in students who got learning by applying of the TAI model.